Hubungan Tingkat Kecemasan Ibu Hamil dengan Kesiapan Menghadapi Persalinan di Klinik Bidan Cikmah Lubis - Febrina Sukmahati; Siska Suci Triana Ginting; Ester Gultom; Juriah Juriah (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
Pregnancy is a natural physiological process that brings various physical and emotional changes, potentially leading to anxiety, especially among first-time mothers (primigravida). The level of anxiety often varies across trimesters, with higher anxiety levels commonly occurring in the first and third trimesters. Uncontrolled anxiety may negatively affect the labor process by increasing pain perception and disrupting uterine contractions.Previous studies have shown mixed results regarding differences in anxiety levels between primigravida and multigravida mothers, as well as its influence on labor preparedness. A preliminary survey conducted at Bidan Cikmah Lubis Clinic in Tanjungbalai City revealed that most third-trimester pregnant women were not adequately prepared for childbirth, which is suspected to be linked to high anxiety levels. Therefore, this study aims to examine the relationship between maternal anxiety levels and childbirth preparedness.